Genome-wide identification of Mg2+ transporters and functional characteristics of DlMGT1 in Dimocarpus longan - Lv, Xinmin; Huang, Shilian; Wang, Jing; Han, Dongmei; Li, Jianguang; Guo, Dongliang; Zhu, Haifeng (Frontiers in Plant Science, 2023)
Longan (Dimocarpus longan) is one of the most important fruit crops in Southern China. Lack of available Mg in acidic soil poses a limitation to further increase longan yield. The Mg transporter (MGT) family MGT/MRS2 mediates the uptake, transport, and redistribution of Mg2+ in higher plants. In our study, we identified 12 D. longan MGTs (DlMGTs). According to protein analyses, DlMGTs were localised in the cell membrane, chloroplast, and nucleus. Phylogenetic analyses revealed the evolutionary differences in MGTs between herbaceous and woody species in different plants. The DlMGT promoters contained many cis-acting elements and transcription factor-binding sites related to the hormone, environmental, and stress responses. Subcellular localisation assays showed that DlMGT1 localises in the cell membrane of tobacco leaf cells. The candidate transcription factor DlGATA16, which may regulate the expression of DlMGT1, was localised in the nucleus of tobacco leaf cells. Dual luciferase analysis demonstrated that DlGATA16 is a potential factor regulating the transcriptional activity of DlMGT1. Herein, we identified and analysed DlMGTs on a genome-wide scale and the subcellular localisation and interaction of DlMGT1 and DlGATA16, which has important implications for further functional analyses of MGTs and the use of MGT for longan genetic improvement.